How stable is the relationship between gang membership and delinquency over time? An exploratory analysis using repeated cross-sectional data from students in one state, 2001-2017 - Watkins, Adam M. (Journal of crime and justice, 2023)
Some ethnographic research suggests that the criminogenic effect of gang membership may not be invariant over time, yet this possibility has gone untested despite the expansive body of research on potential moderators of gang involvement. This research used nine years of self-report data from high school students in Massachusetts (N = 22,120) to explore whether the effect of gang membership on delinquency was moderated over the survey period: 2001 to 2017. The dependent variables included physical fighting, weapon and gun carrying, and drug use and access. The findings suggest that the effect of gang membership on physical fighting and weapon carrying significantly weakened toward the end of the survey period, although this dissipation was not gradual or linear over the survey period. The implications of these findings are discussed with the aim of identifying future avenues of research that could be completed to further examine the role of time period on gang membership.